REVISION TAXONOMICA DEL GENERO BUTLERIA (LEPIDOPTERA: HESPERIINAE) - Herrera, José; MacNeill, C. Don; Atria, Juan (Acta Entomológica Chilena, 2022)
The more recent revisión of this genus is by Hayward (1950) and Evans (1955), who didn’t consider female genitalia as a differentiating character, a feature that the present authors have consistently used in groups like this with extreme variations in its species and a number of other characters are considered as well. This paper proposes that Butheria comprise three subgnera; subgenera (Butleria) with one species, flavomaculata and three subspecies, i.e./. flavomaculata, f. valdiviano, and /. tristriata-, subgenera nov, (Nivis) with three species, paniscoides, elwesi and quilla, the first of which ineludes as subspecies p. paniscoides and p. polyspila’, subgenera nov, (.Marthae) which has four species, bissexguttata,fruticolens, sotoi and philippii, this latter validated in this paper as a legitimate species. The large member of specimens illustrated makes farther description unnecessary.